1994
DOI: 10.1128/aem.60.8.2704-2710.1994
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Yields of Iron-Oxidizing Bacteria by In Situ Electrochemical Reduction of Soluble Iron in the Growth Medium

Abstract: An electrochemical apparatus for culturing chemolithotrophic bacteria that respire aerobically on ferrous ions is described. Enhanced yields of the bacteria were achieved by the in situ electrochemical reduction of soluble iron in the growth medium. When subjected to a direct current of 30 A for 60 days, a 45-liter culture of Thiobacillus ferrooxidans grew from 6 x 107 to 9.5 x 109 cells per ml. Growth of the bacterium within the electrolytic bioreactor was linear with time. A final cell density corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…These results demonstrate that electrodes can serve as an electron donor for microbial reduction of electron acceptors in Geobacter species. Although electrodes have previously been used to regenerate Fe(II) from Fe(III) as an electron donor in the metabolism of Acidithiobacillus (formerly Thiobacillus) (Blake et al, 1994), to our knowledge, the results presented here demonstrate for the first time that electrodes have been found to serve as direct electron donors. As discussed below, this finding has potential applications for manipulating microbial respiration in anaerobic sedimentary environments.…”
Section: Discussionmentioning
confidence: 70%
“…These results demonstrate that electrodes can serve as an electron donor for microbial reduction of electron acceptors in Geobacter species. Although electrodes have previously been used to regenerate Fe(II) from Fe(III) as an electron donor in the metabolism of Acidithiobacillus (formerly Thiobacillus) (Blake et al, 1994), to our knowledge, the results presented here demonstrate for the first time that electrodes have been found to serve as direct electron donors. As discussed below, this finding has potential applications for manipulating microbial respiration in anaerobic sedimentary environments.…”
Section: Discussionmentioning
confidence: 70%
“…Further reactor development strategies will also likely lead to increased productivities. For example, in situ electrochemical reduction of Fe 3þ (Blake et al, 1994) has succeeded in increasing Fe 2þ delivery to wild type A. ferrooxidans cells without precipitation. Cell retention techniques, such as cross flow filtration, may also be used to keep a high cell densities in the reactors which may dramatically improve the productivity of an A. ferrooxidans continuous process.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is no need to add Fe(II) ions during electrochemical cultivation, the concentrations of Fe(II) and Fe(III) are kept low, and inhibition of growth is minimized. The most recent report regarding electrochemical cultivation of T. ferrooxidans indicated that cell densities of 9.5 × 10 9 cells/mL were obtained, which corresponds to a 50-100-fold increase in yield over conventional batch cultivation (Blake et al, 1994). However, when grown by electrolytic cultivation, cell numbers did not increase logarithmically, and it required longer periods of time to achieve the reported high cell densities.…”
Section: Introductionmentioning
confidence: 96%